Pengaruh Sektor Pariwisata terhadap Pengangguran di Provinsi Bali - I Made Putra Yasa; Ida Ayu Meisthya Pratiwi; Made Sinthya Aryasthini Mahaendrayasa (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
The tourism sector plays an important role in the economy of Bali Province. The aim of this research is to analyze the influence of the number of tourist visits and length of stay on unemployment in Bali Province. This research design uses an associative quantitative method which aims to determine the relationship between the number of tourist visits and length of stay on the number of unemployed in Bali Province in 2004-2023. The number of observations in this study was 20 years. The data analysis technique in this research is to use multiple linear regression analysis. The results of the analysis show that the number of tourist visits has a negative and significant effect on the number of unemployed in Bali Province in 2004-2024. Length of stay is negative and significant on the number of unemployed in Bali Province in 2004-2024. The number of unemployed in Bali Province in 2004-2024 can be explained by 73.5 percent by the variables of number of tourist visits and length of stay. Although the number of tourist visits and length of stay have a significant influence on the unemployment rate in Bali, the challenges faced in the tourism sector require a more comprehensive approach.